Delayed Presentation of Intussusception with Perforation after Splenectomy in Patient with Blunt Abdominal Trauma. (17th December 2013) - Afifi, Ibrahim; Al-Thani, Hassan; Attique, Sajid; Khoschnau, Sherwan; El-Menyar, Ayman; Latifi, Rifat
Abstract : Adult intussusception (AI) following blunt abdominal trauma (BAT) is a rare surgical condition. We present a case of delayed diagnosis of ileocecal junction intussusception with a perforation of small bowel in a 34-year-old male with a history of fall from height. Initial exploratory laparotomy revealed shattered spleen requiring splenectomy. Initial abdominal computerized tomography scanning (CT) scan showed dilated small bowel with no organic obstruction. Patient started to improve with partial distention and was shifted to rehabilitation unit. On the next day, he experienced severe abdominal distention and vomiting. Abdominal CT showed characteristic intussusception at the distal ileum. Secondary exploratory laparotomy revealed severe adhesions of stomach and small bowel to the anterior abdominal wall with dilated small bowel loops and intussusception near the ileocecal junction with perforation of small bowel. The affected area was resected and side-to-side stapled anastomosis was performed. Though small bowel intussusception is a rare event, BAT patients with delayed symptoms of bowel obstruction should be carefully evaluated for missed intussusception.